PEMANFAATAN SAMPAH UNTUK MENUMBUHKAN KESADARAN DAN KENYAMAN LINGKUNGAN DI PULAU UNTUNG JAWA, KEPULAUAN SERIBU - Bastuti, Sofian; Muryanto, Heri; F, Wakhit Ahmad; Purwanto, Yusuf; Septiyanto, Andri (LPPM Universitas Pamulang, 2020)
Garbage is one of the complex problems faced by developing countries and developed countries in the world, including Indonesia. Waste problem is no longer just a matter of cleanliness and the environment, but has become a social problem that has the potential to cause conflict. Untung Java Island has an area of 40.10 ha, geographically the island of Untung Jawa is located close to the mainland of Tanjung Pasir and Greater Jakarta. As a tourist attraction, Untung Jawa Island cannot be separated from the problem of garbage or waste. Some garbage is on the coast. The method used to solve the problem of waste utilization is counseling method, discussion method and simulation method. The basic thing offered to help solve the problem is through the activities of fostering and mentoring the local community of Untung Jawa Island, which is packaged with the name of the activity of Utilizing Trash Can in Various Angles to Grow Environmental Awareness and Cleanliness. Of the 50 family heads in kelurahan fortunately in Java, most of the responses were positive with results that did not care for 4 people or 8%, it was normal for 18 people or 36%, Caring for 15 people or 30%, Very concerned for 13 people or 26%.